Metallic ground states of undoped Ti2O3 films induced by elongated c-axis lattice constant - K. Yoshimatsu (Nature Portfolio, 2020)
Abstract Ti2O3 exhibits unique metal–insulator transition (MIT) at ~ 450 K over a wide temperature range of ~ 150 K. The close relationship between MIT and crystal deformation has been proposed. However, as physical properties are governed by the thermodynamic equilibrium in bulk systems, conducting experimental studies under different lattice deformations remains challenging. Epitaxial thin films can offer high flexibility to accommodate adaptive crystal lattices and provide efficient platforms for investigating the MIT. In this study, we report the synthesis of corundum-type Ti2O3 films on various growth temperatures. We found that the metallic ground states appeared in the films grown at low temperatures. The electronic ground states were further investigated by the electronic-structure calculations. Results suggest that the electrical properties of Ti2O3 films were governed by the c/a ratio of the crystal structure, and the absence of the MIT was attributed to the lattice deformation characterized by an elongated c lattice constant.